Effectiveness Of SAVI Method With Reading Group Map Investigation (RGMI) Learning Model In Improving Students' Activity And Learning Achievement Of Grade V - adhel, Risda sulfiana; Supriadi, Supriadi; Nasaruddin, Nasaruddin (ALENA : Journal of Elementary Education, 2025)
In initial observation in October 2024, students showed a lack of enthusiasm, focus on learning and difficulty in understanding subjects concepts. This study aimed to determine the application and effectiveness of the somatic, auditory, visual, intellectual (savi) method and the reading group map investigation (RGMI) learning model in improving the activity and learning achievement of fifth grade students of UPT SPF SD Kalukuang 1 Makassar. The type of research used was pre-experiment using quantitative research methods. The population and sample of this study were all fifth grade students totaling 28 people. The results of the study showed that the application of the SAVI method and the RGMI learning model had an effect seen from the activity and achievement of students. The SAVI method and the RGMI learning model of fifth grade students of SD Kalukuang 1 Makassar had a significant effect on the activity and achievement of fifth grade students after obtaining the results of the hypothesis test with a significance of 0.000 <0.5 meaning. There was a significant effect between the SAVI method and the RGMI learning model in improving the activity and achievement of fifth grade students of SD Kalukuang 1 Makassar.